2016
DOI: 10.1016/j.fuproc.2015.09.015
|View full text |Cite
|
Sign up to set email alerts
|

CO2 capture by calcium aluminate pellets in a small fluidized bed

Abstract: Synthetic pellets made using calcium aluminate cement and quicklime have been examined in a small fluidized bed reactor to determine their performance in cyclic CO2 capture for up to 20 calcination/capture cycles. Two batches were examined one a "fresh" batch, and the second an "aged" batch of pellets and their performance was compared with the original parent limestone. Carbonation was carried out at 650 ˚C and calcination at 900 ˚C, both with 15 % CO2, balance N2, as a synthetic flue gas.Experiments were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 47 publications
3
20
0
Order By: Relevance
“…Mechanical strengths of Ca–Al and Ca–Al–Fe were not only significantly promoted in comparison with Ca, but also competitive when comparing with the value (70.9 n ) of a core‐in‐shell CaO–cement absorbent in a previous study . The result of this work was consistent with a previous study which verified that Ca 12 Al 14 O 33 was favorable to enhance mechanical strength of Ca–Al absorbent . Moreover, the elevated mechanical strength of Ca–Al–Fe indicated that Ca 12 Al 14 O 33 was still efficient though this component experienced additional sol–gel processing by citric acid and further calcination at 900 °C in the secondary iron synthesis step (as shown in Figure ).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Mechanical strengths of Ca–Al and Ca–Al–Fe were not only significantly promoted in comparison with Ca, but also competitive when comparing with the value (70.9 n ) of a core‐in‐shell CaO–cement absorbent in a previous study . The result of this work was consistent with a previous study which verified that Ca 12 Al 14 O 33 was favorable to enhance mechanical strength of Ca–Al absorbent . Moreover, the elevated mechanical strength of Ca–Al–Fe indicated that Ca 12 Al 14 O 33 was still efficient though this component experienced additional sol–gel processing by citric acid and further calcination at 900 °C in the secondary iron synthesis step (as shown in Figure ).…”
Section: Resultssupporting
confidence: 89%
“…Stendardo et al verified the stability of CaO–Ca 12 Al 14 O 33 for capturing CO 2 under severe calcination condition (1000 °C, 85% CO 2 , and up to 200 cycles). Blamey et al revealed that attrition resistance of CaO–Ca 12 Al 14 O 33 was significantly improved in a small fluidized bed, comparing with CaO. The aforementioned researches provided useful reference for the enhancement of cyclic carbonation reactivity and mechanical strength of CaO‐based absorbent.…”
Section: Introductionmentioning
confidence: 99%
“…All samples contained the basic compound CaO. In Ca‐Al and Fe/Ca‐Al absorbents, Ca 12 Al 14 O 33 was observed, which could be beneficial to enhance the multicycle CO 2 absorption and calcium‐based absorbents' mechanical strength 46,49 . Raman spectra with peaks at 1080 cm −1 (Figure S3) verified the existence of free oxygen (O 2 − ) and Ca 12 Al 14 O 33 in the two absorbents 64 .…”
Section: Resultsmentioning
confidence: 82%
“…The stability of the CaO–Ca 12 Al 14 O 33 absorbent under multicycle carbonation–calcination conditions has been verified by varying the mass ratios of CaO to Ca 12 Al 14 O 33 46,47 and under mild 46 or severe 48 calcination conditions. Meanwhile, the attrition resistance of CaO–Ca 12 Al 14 O 33 has been examined by fluidized bed tests, which reveal that the mechanical strength can be obviously promoted compared to conventional CaO 49 . The aforementioned research gave beneficial references for promoting the mechanical strength and cyclic CO 2 absorption stability of calcium‐based absorbents.…”
Section: Introductionmentioning
confidence: 98%
“…Further testing was performed on the steel‐slag‐derived sorbent obtained under the optimum acid pretreatment conditions (denoted CAS). Granulation of steel‐slag‐derived sorbent powder is necessary during practical CO 2 capture process, because the sorbent fines are easily elutriated from the CLP , . Therefore, cylindrical pellets, denoted CAS‐E, with a diameter of 1 mm were prepared by using an E25 extruder.…”
Section: Resultsmentioning
confidence: 99%